The Effectiveness of Family Systems Counseling on the Academic and Emotional Functioning of Adolescents with Parents Involved in Marital Conflict - Pishbin, MohammadSadegh; Gorjinzhad, Simindokht; Azami, Erfan; Safdary Magherloo, Elnaz (Mental Health and Lifestyle Journal, 2024)
The present study was conducted to examine the effectiveness of family systems counseling on the academic and emotional functioning of adolescents whose parents are involved in marital conflict. This applied research employed a quantitative, quasi-experimental method with a pretest–posttest design and a control group. The statistical population included all adolescents aged 12 to 16 in Shiraz in 2025. Using purposive sampling, the researcher selected 40 adolescents with parental conflicts from among all lower- and upper-secondary school students. The participants were randomly assigned into two groups: 20 in the experimental group and 20 in the control group. The experimental group received Bowen family systems counseling. At the field level, data were collected using the Academic Performance Questionnaire developed by Pham and Taylor and the Emotion Regulation Questionnaire designed by Gross and John (2003). The quantitative variables were analyzed using SPSS software version 28. In addition, analysis of covariance was applied to test the research hypotheses. The results indicated that family systems counseling had a significant positive effect on increasing cognitive reappraisal. Family systems counseling had a significant effect on reducing expressive suppression, and it also had a significant effect on improving academic performance.